Sticking to the social mission: Microinsurance in bottom of the pyramid markets. (July 2019) - Elango, B; Chen, Stephen; Jones, Jim
The purpose of this article is to understand what drives social enterprises in bottom of the pyramid (BOP) markets to stick to or drift away from their social mission. Based on an analysis of 192 microinsurance operators in 26 emerging markets, we find that (1) when donors are involved in the operations of the social enterprise, this leads to a greater commitment to the social mission and (2) social enterprises located in countries with poorly performing governments tend to have a lower commitment to their social mission. Given the need for social services in such countries, we offer some suggestions to increase the chances of social enterprises staying committed to their social mission.